2007
DOI: 10.1149/1.2727404
|View full text |Cite
|
Sign up to set email alerts
|

On the Depth Profiling of the Traps in MOSFET's with High-k Gate Dielectrics

Abstract: A general and reliable model for charge pumping (CP) proposed recently has been extended to trap depth distributions towards oxides depth. The fundamental features concerning the energy and depth region probed at the Si-SiO2 interface and in the direction of oxides depth are presented in the case of the different basic CP curves. The effect of the electric field is accounted for and its impact on the results is discussed. Then, MOSFET's with HfO2 gate dielectric are studied. Trap depth concentration profiles r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has been reported that doping La into other high-k materials can also achieve improvements, and the most important effect of La doping is to passivate the oxygen vacancies in other high-k binary oxides. After several reports showing that La incorporated in HfO 2 could significantly improve the device performance [53][54][55][56][57][58][59][60][61][62][63][64][65][66], X. P. Wang et al proposed that this improvement should be ascribed to the reduction of oxygen vacancies (V O ) in HfLaO [66]. Therefore, several studies on the physics of this phenomenon have been made and confirmed the V O passivation role of La as discussed below.…”
Section: Effects Of La On La-doped Ternary Oxidesmentioning
confidence: 84%
See 4 more Smart Citations
“…It has been reported that doping La into other high-k materials can also achieve improvements, and the most important effect of La doping is to passivate the oxygen vacancies in other high-k binary oxides. After several reports showing that La incorporated in HfO 2 could significantly improve the device performance [53][54][55][56][57][58][59][60][61][62][63][64][65][66], X. P. Wang et al proposed that this improvement should be ascribed to the reduction of oxygen vacancies (V O ) in HfLaO [66]. Therefore, several studies on the physics of this phenomenon have been made and confirmed the V O passivation role of La as discussed below.…”
Section: Effects Of La On La-doped Ternary Oxidesmentioning
confidence: 84%
“…After several reports showing that La incorporated in HfO2 could significantly improve the device performance [53-66], X. P. Wang et al proposed that this improvement should be ascribed to the reduction of oxygen vacancies (VO) in HfLaO [66]. Therefore, several studies on the physics of this phenomenon have been made and confirmed the VO passivation [60], (e) Si 1s spectrum at the La 2 O 3 /Si interface for different annealing temperatures [57], and (f) XRD patterns of La 2 O 3 and LaON films after annealing [61].…”
Section: Effects Of La On La-doped Ternary Oxidesmentioning
confidence: 97%
See 3 more Smart Citations